First year nursing students use of social media within education: Results of a survey. (February 2018) - Price, Ann M.; Devis, Kate; LeMoine, Gayle; Crouch, Sarah; South, Nicole; Hossain, Rosa
Abstract: Introduction: Social media rapidly disseminates information but is a controversial learning platform in nurse education. This study aimed to explore how students viewed the use of Twitter, and other social media, in their first year of a nursing degree. Aim: The aim of this study was to evaluate first year student nurses' use of social media, before and after commencing a pre-registration programme, where Twitter was used in a module. Methodology: A cross-sectional approach using a descriptive survey was completed. Methods: An online survey, that included Likert scale and open questions, was open for one month in 2016. Sample: All students on Nursing Undergraduate Degrees, in Adult, Child and Mental Health, who were in the first year of their programme were eligible to participate. 121 students took part with a response rate of 32%. Results: Most students were positive about using social media as they found it an engaging way to promote discussion and share information. Students use of Twitter changed in the first year with 19.8% using it once or more per week on commencement of the programme which increased to 45.5%; other social media platforms remained static. Most students (57.8%) understood the purpose of using Twitter although 14% reported that it was not used within their module; thus, not all students gained experience of using the social media. 81% of students said that using Twitter had been beneficial to increase awareness of nursing issues within their course. However, there were areas that students found difficult such as time, and not knowing what to say. Conclusion: The study suggests that teaching about social media, and incorporating it into learning activities, may be beneficial for students. However, more research into the subject using an experimental design to assess changes over time would be useful. Highlights: Students find the use of social media an engaging and informative approach to learning. Teaching a tool, such as Twitter, to students' increases its use within the learning setting. Students need lecturers to be engaged with social media activities to stimulate use of the approach. Some students are wary about using social media for professional and learning reasons, so individual factors are important.